Ovarian Hemangioma Presented as an Incidental Ovarian Mass: A Rare Case Report along with Literature Review - Nakuci, Daniela; Kola, Erisa; Horjeti, Edlira; Kola, Ina; Shaipi, Blerona; Musa, Juna; Guy, Ali; Alimehmeti, Mehdi (Archives of Clinical and Medical Case Reports, 2020)
Vascular malformation tumors in the female genital tract, especially those arising in the ovary are uncommon with low morbidity. Ovarian hemangioma (OH) featured as a benign rare tumor occurs among adults and children with the age ranging from infancy till octogenarian. Moreover, it presents as an obscured landscape in the backdrop of other gynecologic issues, making hard accuracy perceiving an isolated diagnosis. Usually asymptomatic cases amid patients are being investigated, remaining in dormant phase for a long time and until simultaneously cohabiting with another primary pathology. Metrorrhagia, a dysfunction uterine bleeding, might be a unique sign or association with suprapubic abdominal pain may suggest a vascular ovarian hemangioma. Here we analyze a case of a 44-year-old female that underwent a surgical intervention of uterine leiomyoma leading to the diagnosis of infrequent latent cavernous and capillary hemangioma in the right ovary with normal tumor markers. Radiologic evaluation settled the symptomatic leiomyoma diagnosis and orientated us to presume an ambiguous investigation as a slightly right adnexa enlargement was recognized. Furthermore, a detailed microscopic examination and immunohistochemistry staining process was significant to confirm the blended type of ovarian hemangioma.